2016
DOI: 10.18203/2320-1770.ijrcog20160567
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour versus conservative management for mild gestational hypertension at term

Abstract: Hypertensive disorders of pregnancy remain a leading cause of maternal and perinatal morbidity and mortality. The management of severe gestational hypertension and preeclampsia at term is clear. The only definitive treatment for the same is delivery. 1 But the management of mild gestational hypertension without any other complication at term is not clear. Induction of labour is thought to prevent the progression of hypertension and its complications like eclampsia, HELLP syndrome, placental abruption, renal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 9 publications
5
7
0
Order By: Relevance
“…9 Majority of the patients in the present study were from rural community (66.67% in group A and 76.67% in group B) and studied only till primary school (40% in group A and 38.33% in group B). The mean systolic pressure and diastolic pressure in both groups in the present study were comparable which was similar to the study conducted by Pallipuram et al 4 It was seen that in the present study, 30% patients from Group B underwent spontaneous onset of labor whereas none (0) from group A underwent spontaneous onset of labor which was significant statistically. The HYPITAT Trial8 showed that 53% patients in expectant group underwent spontaneous onset of labour as compared to 3% patients in induction group.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…9 Majority of the patients in the present study were from rural community (66.67% in group A and 76.67% in group B) and studied only till primary school (40% in group A and 38.33% in group B). The mean systolic pressure and diastolic pressure in both groups in the present study were comparable which was similar to the study conducted by Pallipuram et al 4 It was seen that in the present study, 30% patients from Group B underwent spontaneous onset of labor whereas none (0) from group A underwent spontaneous onset of labor which was significant statistically. The HYPITAT Trial8 showed that 53% patients in expectant group underwent spontaneous onset of labour as compared to 3% patients in induction group.…”
Section: Discussionsupporting
confidence: 91%
“…It was similar to the study of Pallipuram et al, and The HYPITAT trial which also reported increased progression to severe hypertension in conservative group in comparison to the induction group. 4,8 Similarly progression to preeclampsia and eclampsia was more in conservative management group as compared to induction group which was also seen in study conducted by Pallipuram et al 4 The present study found increased incidence of PPH in the conservative group in comparison to the induction group which was similar to the study conducted by Pallipuram et al 4 and The HYPITAT trial. 8 They found no incidence of abruption in either group, whereas in the present study Group B had slightly increased incidence of abruption cases compared to Group A (3.33% vs. 1%) although the differences were not significant statistically.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations